Outbreak of P.3 (Theta) SARS-CoV-2 emerging variant of concern among service workers in Louisiana - Rebecca Rose; David J. Nolan; Tessa M. LaFleur; Susanna L. Lamers (Elsevier, 2022)
During routine industrial quarantine/premobilization procedures, four individuals who recently traveled from the Philippines tested positive for SARS-CoV-2. Subsequent genomic analysis showed that all four were infected with a relatively rare Variant of Interest (P.3, Theta) derived from a single origin. This demonstrates the importance of on-going genomic surveillance of SARS-CoV-2.